Hybrid, Unique and Collectible Models: Toward a Semiotics of Consumption in the Metaverse - Terracciano, Bianca (E|C, 2023)
Metaverse evokes a second spatiality, that of purchase, first virtual, then actualized as the only way to adhere to the object and thus the value system, in a consumption scenario in which consumer goods are increasingly rare and limited editions. Achieving the purchase is no longer a playful aesthetic experience but a glorifying trial in which status recognition is at stake. Following instructions also means adhering to the imposed corporeality to maintain a reputation, which means representing oneself i ntersubjectively. For example, not being able to obtain an expensive NFT excludes one from a cultural niche, a form of life, or a way of telling a story. If the nature of the experience is not substantial, it cannot even be called imaginary because it is e xperienced as a pleasure that finds its expression in the process of search and choice. The mere visual contact with the good, placed in a digital public context, actualizes the desire for consumption. Thus, aesthetic satisfaction and self esteem could rep lace the deprivation of material substance in the metaverse. So, it is necessary to explore the metaverse from the Latourian perspective and observe it starting from the hybridization.